Dual gradient-echo MRI of post-contraction changes in skeletal muscle blood volume and oxygenation - Damon, Bruce M.; Hornberger, Jennifer L.; Wadington, Megan C.; Lansdown, Drew A.; Kent-Braun, Jane A. (Magnetic resonance in medicine, 2007)
Analysis of post‐contraction MRI signal intensity (SI) transients may allow noninvasive studies of microvascular reactivity and blood oxygenation recovery. The purpose of this study was to determine the physiological basis for post‐contraction changes in short‐echo (6 ms) and long‐echo (46 ms) gradient‐echo (GRE) MRI signals (S6 and S46, respectively). Six healthy subjects were studied with the use of dual GRE MRI and near‐infrared spectroscopy (NIRS). S6, S46, total hemoglobin concentration ([THb]), and oxyhemoglobin saturation (%HbO2) were measured before, during, and after 2 and 8 s dorsiflexion maximal voluntary contractions, and 5 min of proximal arterial occlusion. The changes in S6 and [THb] after the 2‐s contractions were similar to those following 8‐s contractions, but changes in %HbO2 and S46 were greater following 8‐s contractions than after the 2‐s contractions. [THb] and S6 did not change during and following 5 min of arterial occlusion, but %HbO2 and S46 were both significantly depressed at similar occlusion durations. Also, distance measures indicated similarity between S6 and [THb] and between S46 and %HbO2. We conclude that following brief human skeletal muscle contractions, changes in S6 primarily reflect changes in blood volume and changes in S46 primarily reflect changes in blood oxygenation. Magn Reson Med 57:670–679, 2007. © 2007 Wiley‐Liss, Inc.